Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Transportasi Online GrabBike Pada Mahasiswa Fakultas Ilmu Sosial Dan Politik Universitas Sam Ratulangi - Soromi, Reinhard K.; Pelleng, Frendy A. O.; Kalangi, Johnny A. F. (Sam Ratulangi University, 2019)
The purpose of this study was to determine the effect of service quality on customer satisfaction using GrabBike online transportation services to students of the Sam Ratulangi University Faculty of Social and Political Sciences. This type of research is quantitative descriptive. The relationship between quality of service and costumer satisfactions assists the costumer in revising its perception of service quality. Data Validity Test Results obtained all statement items declared valid. Data reliability test results of data obtained are stated that the data is reliable. The results of simple linear regression cost value more then the regression coefficient so that the regression coefficient is positive. The results of hypothesis test based on the significance value of the Coefficients table obtained significance, so that it can be concluded that the service quality variable affects the variable customer satisfaction. The test results of the coefficient of determination Adjusted R Square value which states the variable customer satisfaction is influenced by service quality variables, while the remaining is influenced by other variables that are not in this study. hence the correlation coefficient, which is included in the strong category so that there is a strong relationship between the quality of service to customer satisfaction and online GrabBike transportation to students of the Faculty of Social and Political Sciences, Sam Ratulangi University.